How Plant Polyhydroxy Flavonoids Can Hinder the Metabolism of Cytochrome 3A4 - Carina S. P. Vieira; Marisa Freitas; Andreia Palmeira; Eduarda Fernandes; Alberto N. Araújo (Biomedicines)
Background/Objectives: Recent interest in dietary components and their effects on xenobiotic metabolism has highlighted their role in modulating drug pharmacokinetics. Cytochrome P450 3A4, a key isoform of the cytochrome P450 superfamily, is involved in the metabolism of over 50% of xenobiotics. Flavonoids, present in various foods and supplements, exhibit diverse biological activities influenced by the structural modifications in their scaffold. Methods: Fifteen polyhydroxy-flavonoid compounds were firstly tested by a high-throughput fluorimetric method for their ability to inhibit CYP3A4, where scutellarein and gossypetin were assessed for the first time. A molecular docking analysis was performed for the most active inhibitors to gain insight on their interaction with the active site of the enzyme. Results: Baicalein, luteolin, and scutellarein were the most potent flavones, presenting an IC50 of 15 ± 5, 31 ± 10, and 19 ± 7 μmol/L, respectively. Gossypetin, herbacetin, and quercetin were the most potent flavonols with IC50 of 40 ± 8, 32 ± 8, and 23 ± 5 μmol/L, respectively. The molecular docking analysis showed that hydroxyl groups at C6, C7, C8 (ring A), and C3’ (ring B) on the flavone structure affect CYP3A4 enzyme catalysis by binding to its substrate-binding site as strong as known antiviral and antifungal drugs. Conclusions: Binding to the enzyme’s active site with a strength comparable to known antifungal and antiviral drugs, baicalein and scutellarein were identified as the most active flavonoids. The vicinal hydroxyls in those molecules were pivotal to positioning and stabilization in the catalytic site pocket.